1980
DOI: 10.1084/jem.152.6.1519
|View full text |Cite
|
Sign up to set email alerts
|

Pre-B cells and other possible precursor lymphoid cell lines derived from patients with X-linked agammaglobulinemia

Abstract: A group of unique Epstein-Barr virus-containing cell lines was derived from the bone marrow of three patients with X-linked agammaglobulinemia. Efforts to obtain cell lines from the peripheral blood of these patients were uniformly unsuccessful. Immunofluorescence analyses as well as biosynthetic studies with [(35)S]methionine indicated unusual patterns of Ig synthesis in many of these bone marrow derived lines. Seven of the lines were of particular interest in that two produced no Ig of any type; two others s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
1

Year Published

1982
1982
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 15 publications
2
20
1
Order By: Relevance
“…In conclusion, we have established LCL with the nature of pre-B cells and other precursor B cells from the bone marrow cells of patients with CAG and confirmed the observation of Fu et al (1980). However, we have found more variable patterns of Ig expression, especially with regard to the expression of 6 heavy chains, in the LCL established in our laboratory.…”
Section: Establishment O F Lcl From Bone Marrow Cells In Gag Patientsmentioning
confidence: 63%
See 1 more Smart Citation
“…In conclusion, we have established LCL with the nature of pre-B cells and other precursor B cells from the bone marrow cells of patients with CAG and confirmed the observation of Fu et al (1980). However, we have found more variable patterns of Ig expression, especially with regard to the expression of 6 heavy chains, in the LCL established in our laboratory.…”
Section: Establishment O F Lcl From Bone Marrow Cells In Gag Patientsmentioning
confidence: 63%
“…Recently, Fu et al (1980) have reported that LCL resembling pre-B cells and other possible precursor cells of B cells have been established from EBV infected bone marrow cells of CAG patients suggesting that precursor B cells without Ig synthesis and pre-B cells without surface Ig (slg) could be transformed by EBV, giving rise to LCL which retain the characters of their cell origin, although the target cells for EBV were considered to be B cells with C3d receptors and slg (Yefenof et al 1976; Katsuki et al 1977). In this study we have established LCL with characteristics of precursor B cells from CAG patients, and demonstrated that the LCL established had more diverse patterns of Ig expression than those reported previously.…”
mentioning
confidence: 99%
“…During lymphocyte ontogeny, BSAP is first expressed at the multipotent pro-B-cell stage and actually drives the final commitment to the B-cell lineage (27); thereafter, it remains expressed in mature B cells and is only extinguished with the final differentiation to a plasma cell (1). It is therefore interesting that both pro-and pre-B cells have been found to be susceptible to EBV transformation in vitro (13,15,20). By contrast, plasma cells are not transformable, and indeed, the plasmacytic differentiation of LCL cells has been linked to lytic cycle induction and the suppression of Wp/Cp activity (9,34).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the LCL from BMM of CAG patients possessed almost the same characteristics as the precursor B cells reported by Fu et al (1980) which lacked slg, clg, and secretion of Ig. They had EBV associated nuclear antigen (EBNA), complement receptors (C3b and C3d), Fe receptors for IgM, Con A receptors, and peanut agglutinin (PNA) receptors.…”
Section: Methodsmentioning
confidence: 49%